Analysis of deposit formation mechanism and structure optimization in urea-SCR system of diesel engine. (1st April 2020) - Huang, Haozhong; Chen, Yajuan; Li, Zhihua; Wang, Hui; Hao, Bin; Chen, Yingjie; Lei, Han; Guo, Xiaoyu
Highlights: A detailed mechanism of urea decomposition was used to analyze the formation process of urea deposition. The structure of the mixer was optimized, and the pressure drop of mixer was reduced. The uniformity indices of NH3 concentration and velocity were improved. Optimization scheme I produces urea solid, biuret, CYA, and ammelide that have the lowest qualities. Abstract: A three-dimensional computational model of a diesel engine exhaust post-treatment system is built in the computational fluid dynamics software to simulate the deposit formation process in the mixer area of the diesel engine Urea-SCR (selective catalytic reduction) system. The SCR inlet uniformity, pressure drop in the mixer, urea solid, and three main urea by-products (biuret (biurea), CYA (cyanuric acid), and ammelide (cyanuric acid monoamide)) are investigated in the exhaust post-treatment system of the diesel engine. The results show that in the whole exhaust post-treatment system, the liquid film only appears in the mixer and nozzle areas. It is found that the production of biuret, CYA, and ammelide, which are by-products of urea decomposition, is mainly affected by the NCO − (isocyanate-group) concentration, and liquid film temperature and height. The thicker the liquid film and the smaller the rate of evaporation, the smaller the mass fraction of urea solid and the larger the mass fraction of urea decomposition by-products. According to the analysis results, the optimization scheme of the mixer is proposed, and the simulation analysis is performed. The analysis results show that the NH3 concentration uniformity at the SCR inlet increases, and the pressure drop in the mixer decreases. The deposits, such as urea solids, biuret, CYA, and ammelide decrease. Consequently, the performance of the exhaust post-treatment system is improved.